Potential Candidate Molecules of Past and Present for Combating High Altitude Hypoxia Induced Maladies - Kushwaha, Shweta; Saraswat, Deepika (Defence Life Science Journal, 2024)
Hypobaric hypoxia occurs at high altitudes where barometric pressure is low causing insufficient supply of oxygen leading to many high-altitude illnesses like acute mountain sickness (AMS), high altitude pulmonary edema (HAPE), high altitude cerebral edema (HACE) etc.Medications have been applied to treat and prevent injuries caused by HBH, showing anti-inflammatory, anti-edemagenic, and antioxidant properties. AMS symptoms, such as headache, nausea, weariness, usually go away in 1-2 days. HACE causes brain swelling, elevated intracranial pressure, resulting in confusion, stupor, ataxia, and death.Acetazolamide, dexamethasone, nifedipine are the drugs used for treatment acting oncarbonic anhydrase enzyme, calcium channels.Acetazolamide increases arterial partial pressure of oxygen.Nifedipine relaxes vascular smooth muscles and increases blood flow. Some drugscause side effects also like dizziness, diuresis, nausea, malaise, etc. Hence, a new drug search is needed to find more targeted and fewer side effects for faster relief and better health at high altitudes.